2002
DOI: 10.5380/cep.v20i1.1140
|View full text |Cite
|
Sign up to set email alerts
|

COMPOSIÇÃO QUÍMICA E PROTÉICO-MOLECULAR DA FARINHA DE RESÍDUOS DE CAMARÃO-SETE-BARBAS ( Xiphopenaeus kroyeri)

Abstract: Caracterizou-se a farinha de resíduos de camarão-setebarbas quanto aos aspectos físico-químicos e análise molecular de proteínas. O corpo do camarão foi utilizado como parâmetro comparativo. Realizou-se estudo das proteínas pela quantificação de N-total, análise colorimétrica e avaliação molecular. Os resíduos apresentaram potencial em relação a dois nichos alimentares: nutricional (mineral) e dietético (alto teor de fibra alimentar e baixo conteúdo lipídico). Verificou-se neste resíduo baixo teor protéico sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Comparing the results of lyophilized flour obtained from waste with those obtained from fresh shrimp waste, it was found that the lyophilized flour showed ash values 2 times higher than values obtained for fresh waste. Freitas et al (2002) studied shrimp waste flour and found values 4 times higher than for fresh shrimp. According to Wang and Hwang (2001), the composition of minerals consists mainly of calcium carbonate, phosphate, magnesium, silicon and sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the results of lyophilized flour obtained from waste with those obtained from fresh shrimp waste, it was found that the lyophilized flour showed ash values 2 times higher than values obtained for fresh waste. Freitas et al (2002) studied shrimp waste flour and found values 4 times higher than for fresh shrimp. According to Wang and Hwang (2001), the composition of minerals consists mainly of calcium carbonate, phosphate, magnesium, silicon and sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…Here we must consider that higher ash content in the shrimp residue flour (25.35% present study) was also reported by other authors: 38.29% (Freitas et al . ), 17.53% (Damasceno, ), 15.75% (Brasileiro et al ., ), and 19.60% (Khan & Nowsad, ). A way to mitigate the higher ash content (above the allowed limit of 3%) is by the reduction in the shrimp residue flour during biscuit making.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this residue has no cost and its rational use can reduce the risk of environmental pollution, contribute to an increase in animal protein consumption and, finally, the insertion of a new ingredient for the food industry (Antunes‐Valcareggi et al ., ). It is justified by the fact that the discarded residue is rich in nutrients, such as high content of chitin (15–20%), proteins (15–40%), inorganic salts (ashes 40–55%) and carotenoid pigments (15%), which would be an important alternative for the food industry (Freitas et al ., ; Damasceno et al ., ; Kandra et al ., ; Antunes‐Valcareggi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the use of shrimp waste in poultry feed may be limited by its ber content (15.38%). Freitas et al (2002) found a high content of dietary ber in the shrimp shell meal, attributing it to chitin, normally present in the shells of crustaceans, and these bers were not digested in the analysis process.…”
Section: Introductionmentioning
confidence: 97%